Unraveling the determinants and consequences of mandatory IFRS convergence in India: insights from systematic literature review - Nikhil M N; Sandeep S. Shenoy; Suman Chakraborty; Abhilash (Cogent Business & Management, 2024)
The last few decades have evidenced radical changes in global standards, particularly the International Financial Reporting Standards convergence in India has piqued the curiosity of researchers and professionals. Despite the evolving research, there is no consensus on its consequences in the Indian context. In this backdrop, this paper provides a state-of-the-art summary of empirical archival on determinants and effects of Ind AS for the post-2010 period. To this end, the study employs the systematic literature review method following the Scientific Procedure and Rationales for the Systematic Literature Review approach. A total of 50 articles retrieved from the Scopus and Web of Science database between 2010 and 2024 were reviewed. The results revealed that the perceived benefits of IFRS, globalization, and the urge to enhance reporting quality are the key drivers of IFRS convergence in India. Regarding impact, the review uncovered that Ind AS has increased the quality of financial reporting, value relevance, and firm performance. However, it has led to a decline in the ethical reporting of the firms. Further, Ind AS witnessed the increased length and complexity of financial statements, causing problems with the readability of the reports. Overall, the observed learning curve effect strongly suggested that the Ind AS will have a favourable impact on the Indian accounting realm moving forward. The findings urge that policymakers should adopt concurrent enforcement mechanisms while investors are advised to exercise caution while making investment decisions.
Keywords: M40; M41; M48; M49; 650; IND AS; compliance and adoption; fair value accounting; accounting disclosure; india; review